2012
DOI: 10.1093/glycob/cws087
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal fragment of axon guidance molecule Slit3 binds heparin and neutralizes heparin's anticoagulant activity

Abstract: Slit3 is a large molecule with multiple domains and belongs to axon guidance families. To date, the biological functions of Slit3 are still largely unknown. Our recent study demonstrated that the N-terminal fragment of Slit3 is a novel angiogenic factor. In this study, we examined the biological function of the C-terminal fragment of human Slit3 (HSCF). The HSCF showed a high-affinity binding to heparin. The binding appeared to be heparin/heparan sulfate-specific and depends on the size, the degree of sulfatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
(55 reference statements)
1
16
0
Order By: Relevance
“…Moreover, fully desulfated heparin (Des-Hep), N-desulfated heparin (N-Des-Hep), and 6-O-desulfated heparin (6-Des-Hep) lost their ability to compete with heparin for SLIT3 binding, whereas 2-O-desulfated heparin (2-Des-Hep) did not ( Figure 6G). Similar binding characteristics have been observed for SLIT3-C (27). These binding measurements were consistent with the effect of Ndst1 deficiency on SLIT-ROBO signaling, reducing both N-and 6-O-sulfation of HS ( Figure 6, B-D).…”
Section: -O-sulfation By 20% (supporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, fully desulfated heparin (Des-Hep), N-desulfated heparin (N-Des-Hep), and 6-O-desulfated heparin (6-Des-Hep) lost their ability to compete with heparin for SLIT3 binding, whereas 2-O-desulfated heparin (2-Des-Hep) did not ( Figure 6G). Similar binding characteristics have been observed for SLIT3-C (27). These binding measurements were consistent with the effect of Ndst1 deficiency on SLIT-ROBO signaling, reducing both N-and 6-O-sulfation of HS ( Figure 6, B-D).…”
Section: -O-sulfation By 20% (supporting
confidence: 87%
“…Recombinant human SLIT3 N-terminal fragment (aa 34-919) was purchased from R&D Systems or was expressed in house. The N-terminal fragment was cloned into a modified pcDNA 3.1 vector (Invitrogen) with an HPC4 tag at the N terminus and a 6x-His tag at the C terminus (27). The construct was transfected into mouse neuroblastoma N2A cells (ATCC), and stably expressing clones were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that Robo1 interacts with heparin/HS, and the interaction is important for Slit2-Robo1 signaling since heparin/HS binds to both Slit2 and Robo1 facilitating the ligand-receptor interaction [24-27]. In our previous report, we used SPR to characterize the binding of Robo1 to heparin immobilized on SA sensor chips [35].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we used Robo1 (Roundabout homolog 1, with or without GFP tagging) in a heparin binding study. Robo1 is the receptor for SLIT1-3 which are thought to act as molecular guidance cue in cellular migration, including axonal navigation at the ventral midline of the neural tube and projection of axons to different regions during neuronal development, and in neovascularization [24-27]. We used surface plasmon resonance (SPR) spectroscopy to study the effect of the GFP tagging on the heparin-binding interactions with Robo1.…”
Section: Introductionmentioning
confidence: 99%